1998
DOI: 10.1089/thy.1998.8.23
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Adhesion Molecule-1 Is Upregulated via the Protein Kinase C Pathway in Human Thyroid Carcinoma Cell Lines

Abstract: Nonantigen specific adhesion systems lymphocyte function-associated antigen 1/intercellular adhesion molecule (LFA-1/ICAM-1) and cluster designation 2/lymphocyte function-associated antigen 3 (CD2/LFA-3) are considered a crucial step in immune-mediated cell-cell adhesion reactions. In particular, the LFA-1/ICAM-1 system is deeply involved in major histocompatibility system (MHC)-restricted and non-MHC-restricted cellular cytotoxicity of effector cells against cancer tissues. We have investigated in human thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…tPA is an agonist of protein kinase C (PKC) (20), and inhibition of PKC can diminish PN death in organotypic cultures initiated at P3 (18). We found that a PKC antagonist, Gö 6976 (2 M), greatly inhibited PN death in nr cerebellar slice cultures initiated at P9 (P Ͻ 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…tPA is an agonist of protein kinase C (PKC) (20), and inhibition of PKC can diminish PN death in organotypic cultures initiated at P3 (18). We found that a PKC antagonist, Gö 6976 (2 M), greatly inhibited PN death in nr cerebellar slice cultures initiated at P9 (P Ͻ 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 83%
“…The possible reason of this discrepancy may depend upon the presence of several adhesion molecules, which display redundant functions in cell-cell adhesion and are all substrates of ADAM17/TACE. For example, a previous report showed the expression of ICAM-1 in thyroid carcinoma cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…ICAM-1 expression is increased by PKC activators such as phorbol ester and phorbol dibutyrate [36,[160][161][162][163] and PKC activity in a variety of cell types is required for the induction of ICAM-1 by inflammatory mediators such as IL-1␤, TNF-␣, IFN-␥, nitric oxide, UVB, and LPS [13,21,82,[164][165][166][167][168][169]. Indeed, pharmacological agents that block PKC activity inhibit induced ICAM-1 transcription, although different PKC isoforms may be involved depending on the cell type and stimuli [161,[169][170][171][172].…”
Section: Pkc Regulation Of Icam-1mentioning
confidence: 99%